Freedom and constraints: A glance at Adventist educational aims - Rondonuwu, Joppi J (JIU (Jurnal Ilmiah Unklab), 2002)
Freedom, in a Christian context, can be a confusing term. Unlike the secular definition of freedom, which includes a lack of restraint, Christian freedom begins with a total surrender to God and His law. Rather than restricting freedom, however, the paradox is that a master-slave relationship with God actually frees the individual from the bondage of sin. Adventist educational should endeavor to foster the harmonious development of the whole person physically, spiritually, intellectually, and socially. Freedom of choice is an important part of that development, and of bringing students into a saving relationship with Christ.